Nebulization as a tool for the delivery of photosensitizers in the photodynamic inactivation of respiratory diseases - Kassab, Giulia (2018)
Pneumonia is one of the main causes of death worldwide, specially of the elderly and the children under 5 years old. The traditional antibiotic-based therapy faces a crisis due to the increase in resistance and a lack of new molecules approved. Recently, our research group demonstrated the photodynamic inactivation of streptococcal pneumonia in vivo, a technique to which the development of resistance is described to be unlikely. This study proposed to investigate the applicability of nebulization as a delivery method for photosensitizers, in the hope to advance the research of the photodynamic inactivation of bacterial pneumonia. First, the critical attributes for nebulization (droplet size and delivery rate), the extent of nebulization, and the stability of three photosensitizers were stablished, and they were all found to be compatible with the technique. Then, the delivery was validated in an animal model using the most promising compound. It was possible to activate it using extracorporeal infrared light without causing acute lung or liver damage. In conclusion, nebulization presented itself as a promising tool for the delivery of photosensitizers to the respiratory tract.